2022
DOI: 10.3390/nu14102153
|View full text |Cite
|
Sign up to set email alerts
|

Extra Virgin Olive Oil Reduces Gut Permeability and Metabolic Endotoxemia in Diabetic Patients

Abstract: Background: Extra virgin olive oil (EVOO) improves post-prandial glycemia, but the underlying mechanism has not been fully elucidated. We tested the hypothesis that EVOO improves post-prandial glycemia by reducing gut permeability-derived low-grade endotoxemia. Methods: Serum levels of lipopolysaccharides (LPS), zonulin, a marker of gut permeability, glucose, insulin and glucagon-like peptide 1 (GLP1) were measured in 20 patients with impaired fasting glucose (IFG) and 20 healthy subjects (HS) matched for sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Indeed, high adherence to the Mediterranean diet has been associated with beneficial microbiome-related metabolomic profiles, an increase in plasma SCFA levels and a reduction in circulating LPS levels compared with low adherence to the Mediterranean diet 126,131,132 . Administration of extra virgin olive oil, a key component of the Mediterranean diet, reduced endotoxaemia and serum zonulin levels and improved the metabolic profile of healthy individuals and patients with impaired fasting glucose 133 . These findings have been corroborated by an interventional study that found decreased circulating levels of LPS in patients with metabolic syndrome who received a fibre-rich diet for 75 days 134 .…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Indeed, high adherence to the Mediterranean diet has been associated with beneficial microbiome-related metabolomic profiles, an increase in plasma SCFA levels and a reduction in circulating LPS levels compared with low adherence to the Mediterranean diet 126,131,132 . Administration of extra virgin olive oil, a key component of the Mediterranean diet, reduced endotoxaemia and serum zonulin levels and improved the metabolic profile of healthy individuals and patients with impaired fasting glucose 133 . These findings have been corroborated by an interventional study that found decreased circulating levels of LPS in patients with metabolic syndrome who received a fibre-rich diet for 75 days 134 .…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Some of the nutraceuticals/drugs that are examined include ferulic acid, melatonin, urolithin A and glucosamine, metformin and berberine, lipoic acid and broccoli sprout extract, and fibrate drugs and astaxanthin. Moreover, the effectiveness of extra-virgin olive oil as a means of reducing gut-permeability-derived low-grade endotoxemia in adults with impaired fasting glucose is presented in a study by Bartimoccia and colleagues [ 14 ].…”
mentioning
confidence: 99%
“…The Mediterranean diet has in general a strong anti-inflammatory effect [ 114 ]. The dominant anti-inflammatory ingredients in this diet are omega-3 fatty acids, olive oil and phenolic compounds, as well as fiber and a low degree of food processing [ 112 , 114 , 115 ].…”
Section: Nutrition—what Is Beyond the Obvious?mentioning
confidence: 99%